2016
DOI: 10.17269/cjph.107.5365
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and preferences of resistance training among older adults in Alberta, Canada

Abstract: OBJECTIVE: The prevalence of resistance training among older adults in Alberta, Canada, has never been measured. Hence, there is no clear understanding of the demographic and health-related factors associated with resistance training, or older adults' resistance training programming preferences. The purpose of this study was to gain a better understanding of resistance training behaviours among older adults in Alberta. METHODS:Older adults (>55 years) from across Alberta were invited to participate in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Our finding of 9.4% of nurses meeting the strength training recommendation is considerably smaller than a previous Canadian study reporting that 53.1% of older adults (>55 years old) met the strength training recommendation (Bampton et al., 2016). However, as described in their study, the unexpectedly high proportion of older adults meeting the strength training recommendation may have been due to response bias, whereby interested adults were over‐represented in the sample.…”
Section: Discussioncontrasting
confidence: 89%
“…Our finding of 9.4% of nurses meeting the strength training recommendation is considerably smaller than a previous Canadian study reporting that 53.1% of older adults (>55 years old) met the strength training recommendation (Bampton et al., 2016). However, as described in their study, the unexpectedly high proportion of older adults meeting the strength training recommendation may have been due to response bias, whereby interested adults were over‐represented in the sample.…”
Section: Discussioncontrasting
confidence: 89%
“…Though the studies available showed beneficial results (i.e., improvements in PA and health measures) and several were culturally tailored to AAs, there is still a need for interventions to utilize tailoring that is appropriate for the intersection of race and male gender. Even though the current study was guided in-part by a conceptual framework developed for older AA women, facilitating the reciprocal coach-type interaction with partners (partners encouraging each other to exercise and supporting each other during exercise) and choosing RT as a key exercise modality were designed to help attract men and retain them in the intervention [41]. The current study did not measure the reasons why participants were interested in participating; however, this is an aspect of mixed-gender dyadic research that should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the factors listed in Table 2 have been identified in previous research as being relevant to seniors' participation in physical activity more broadly. In particular, the importance of social interaction as a motivator for older people is well recognized (Andreasson et al, 2016;Bampton, Johnson, & Vallance, 2016;Barrett & Smerdely, 2003;Farrance, Tsofliou, & Clark, 2016;Henwood et al, 2011;Lübcke et al, 2012;Rydeskog et al, 2005). Similarly, the relevance of instructor quality (Bethancourt et al, 2014;Burton et al, 2017;Farrance et al, 2016;Lübcke et al, 2012), cost (Barrett & Smerdely, 2003), accessibility (Bethancourt et al, 2014;Lübcke et al, 2012), time constraints (Lübcke et al, 2012;Van Roie, Bautmans, Coudyzer, Boen, & Delecluse, 2015), and the nature of other patrons (Rydeskog et al, 2005) has been noted.…”
Section: Discussionmentioning
confidence: 99%